2005
DOI: 10.1016/j.chembiol.2005.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Interactions with Chemically Diverse Stabilizing Agents: Thermodynamics of Binding to the Paclitaxel Site Predicts Cytotoxicity

Abstract: The interactions of microtubules with most compounds described as stabilizing agents have been studied. Several of them (lonafarnib, dicumarol, lutein, and jatrophane polyesters) did not show any stabilizing effect on microtubules. Taccalonolides A and E show paclitaxel-like effects in cells, but they were not able to modulate in vitro tubulin assembly or to bind microtubules, which suggests that other factors are involved in their cellular effects. The binding constants of epothilones, eleutherobin, discoderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
278
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 213 publications
(294 citation statements)
references
References 37 publications
13
278
1
2
Order By: Relevance
“…Standard work-up (CH 2 Cl 2 ) and column chromatography on silica gel (hexanes-EtOAc mixtures) afforded the desired silylated derivative. Compounds 16,34,42, 50 and 52 were prepared in this way (yields are indicated in the corresponding Schemes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard work-up (CH 2 Cl 2 ) and column chromatography on silica gel (hexanes-EtOAc mixtures) afforded the desired silylated derivative. Compounds 16,34,42, 50 and 52 were prepared in this way (yields are indicated in the corresponding Schemes).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were fixed with 70% ethanol, treated with RNase and stained with propidium iodide as previously described. 42 The analysis was performed with a Coulter Epics XL flow cytometer.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…They act as microtubule stabilizers by binding to another microtubule site than taxol resulting in the formation of microtubule bundles and leading to cell cycle arrest and apoptosis. It is also reported that taccalonolides bind to β-tubulin near the lumen of microtubule, which is diferent from the taxol-binding site stabilizers which bind to α-tubulin protoilaments [46][47][48][49].…”
Section: Mechanism Of Action Therapeutic Use Referencesmentioning
confidence: 99%
“…Binding constants of epothilone analogues 2, 3, 6-8 for glutaraldehyde-stabilized microtubules (MTs) were determined at 35 8C by the method previously described by Buey et al, [30] which is based on the displacement of Flutax-2. Binding constants were calculated using Equigra v. 5.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, we also determined the MT binding constants of compounds 2 and 3 using methodology that was developed previously in one of our laboratories and involves the displacement of the fluorescent paclitaxel derivative Flutax-2 from stabilized MTs. [30] …”
Section: C3-modified Epothilonesmentioning
confidence: 99%